Heuristic decision making. [article]. - Gigerenzer, Gerd
As reflected in the amount of controversy, few areas in psychology have undergone such dramatic conceptual changes in the past decade as the emerging science of heuristics. This research indicates that individuals and organizations often rely on simple heuristics in an adaptive way, and ignoring part of the information can lead to more accurate judtgements thatn weighing and adding all information, for instance for low pedicatability and small samples. The big future challenge is to develop a systematic theory of the building blocks of heuristics as well as the core capacities adn environmental structures these exploit.- (from the authors)